The Influence of Self-Efficacy and Self-Esteem on Students’ English Achievement at SekolahTinggi Teknologi Dumai - Julanos Julanos (LINGUA LITERA : journal of english linguistics and literature, 2019)
English achievement is the academic performance through curricular and co-curricular performance of the students in English subject, which indicates the learning outcome of the students in learning English. The differences in English achievement are influenced by various factors such as their self-efficacy and self-esteem. The main purpose of the study was to find out the influence of self-efficacy and self-esteem on students’ English achievement at Sekolah Tinggi Teknologi Dumai. This research was a correlational study conducted at this institution. The participants of the study were 112 students who were selected randomly from 131 students of the third semester of Sekolah Tinggi Teknologi Dumai. A set of questionnaire of English self-efficacy beliefs constructed by Rahemi was used to find out the students’ self-efficacy, and a set of questionnaire of Resenberg self-esteem constructed by Rosenberg was used to find out the students’ self-esteem. The findings of the study indicated that self-efficacy and self-esteem gave a significant influence to the students’ English achievement. Therefore, the proper degree of self-efficacy and self-esteem could encourage students to achieve better English learning achievement.